A Hierarchy of Healing: Origins of the Therapeutic Order and Implications for Research - Finnell, John S (Integr Med (Encinitas), 2019)
The philosophy, principles, and theories of naturopathic medicine include the six Principles of Naturopathic Medicine and the Therapeutic Order. Together these constructs, describe the core principles of the practice of naturopathic medicine, as established by thought leaders throughout the formation and development of the profession. The naturopathic medicine research agenda (NMRA) set forth recommendations for the codification of the foundational theories of naturopathic medical practice. The “Therapeutic Order, Whole-systems, Evidence-based Research Standards” (TOWERS) initiative is proposed with the primary objective to conduct the rigorous evaluation of the Principles of Naturopathic Medicine and the Therapeutic Order constructs. It is envisioned that this initiative will result in the development of an evidence-base concerning the clinical theory, philosophy and principles of whole-systems naturopathic medicine. After over one hundred years of professional organization and formal practice, there is a need to translate these empirically derived constructs into an evidence-informed theory of naturopathic medicine.